Viticultural regions in function of the development of wine tourism - Meri Nickova (UTMS Journal of Economics, 2021)
During the last decade, wine tourism has been intensively developed through small wineries in several viticultural regions in the Republic of North Macedonia. Wine tourism has an important role in creating tourism development policies in the country. Wine tourism is a tourist form that is characterized by attractive attributes through which it encourages domestic and foreign tourists to visit the destination. In addition to visiting the wine cellars, wine tourism includes additional tourist activities such as the process of grape production, the process of wine production, gastronomic offer, sightseeing of the viticultural region. The main for the existence of wineries as a leading factor of wine tourism are the viticultural regions together with the tradition of growing grapes. Viticultural regions define the spatial distribution of wineries and define wine routes. Therefore, in this paper the author aims to present the main viticultural regions in the country which are the spatial basis and prerequisite for the development of wine tourism.
Keywords: L83; Z32; I15; O18; 330; wine routes; tourism offers; vineyards; development; wine regions